How Dynamic Capabilities Drive Development Effectiveness: Empirical Evidence From The World Bank Group In Indonesia - Afandi, Mochammad Farid; Singh, Sanju Kumar (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2026)
Multilateral development organizations are increasingly expected to deliver effective results in environments characterized by uncertainty, complex stakeholder landscapes, and evolving policy priorities. Yet limited empirical evidence explains how internal organizational capabilities translate into perceived development effectiveness. This study examines whether the World Bank Group’s ability to sense stakeholder needs translates into effectiveness through the sequential activation of seizing and reconfiguring capabilities within the context of Indonesia’s development portfolio. Using stakeholder perception data from the Indonesia Country Opinion Survey and a serial mediation design, the analysis tests a theory-driven model in which sensing capability influences effectiveness through resource mobilization and adaptive partnership adjustment. Results reveal that sensing capability does not directly predict perceived effectiveness once mediating mechanisms are considered. Instead, its influence operates fully through indirect pathways. The dominant mechanism runs through seizing capability, indicating that the ability to deploy sector expertise across domains such as human capital, infrastructure, institutions, and sustainability constitutes the primary channel through which effectiveness is realized. Reconfiguring capability provides an additional but smaller contribution, reflecting the role of responsiveness and flexibility in sustaining alignment with evolving development needs. The full sequential pathway from sensing through seizing and reconfiguring to effectiveness is statistically supported, demonstrating that adaptation functions as an integrated process rather than a set of independent activities. These findings advance understanding of how dynamic organizational processes shape development outcomes and suggest that strengthening technical delivery capacity and institutional adaptability may be more consequential than investments in diagnostic capability alone. The study highlights the importance of examining internal capability mechanisms to better understand how development institutions convert environmental awareness into stakeholder-recognized results.